An animal model manifesting neurodegeneration and obesity - Susaki, Etsuo (Impact Journals LLC, 2010)
Although the existence of a link between neurodegenerative diseases and obesity has been suggested, a causal relation between neural degeneration and obesity has remained to be demonstrated experimentally. We recently showed that neurodegeneration in the hypothalamic satiety center results in obesity in mice transgenic for E4B (also known as UFD2a), a mammalian ubiquitin elongation factor (E4). Increased expression of E4B in neurons of the transgenic mice results in the formation of ubiquitin-positive aggregates similar to those apparent in many human neurodegenerative diseases as well as in degeneration of hypothalamic neurons responsible for the regulation of food intake and energy expenditure. We thus propose that neurodegeneration is a possible cause of human obesity and related metabolic diseases, which have become a serious public health problem worldwide. Our animal model is thus a powerful tool for studies of the relation between neurodegeneration and obesity.